Fuzzy Analytic Hierarchy Process (FAHP) Integrations for Decision Making Purposes: A Review - Mohamed Noor, A. Z.; Md Fauadi, M.H.F.; Jafar, F.A.; Nordin, M.H.; Yahaya, S.H.; Ramlan, S.; Shri Abdul Aziz, M.A. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Fuzzy Analytic Hierarchy Process (FAHP) is generally used as decision making purpose. However, AHP provides a single numerical number. As the method can only yield binary decisions of either “yes” or “no”, the method is not compatible when the decision has uncertainties. Consequently, previous researchers have fused AHP with fuzzy to process alternatives with uncertainty judgment. In this paper, fundamental knowledge of separate tool was reviewed. Fundamental of both fuzzy and AHP were also summarized in this article. The next phase of this paper was to split the types of FAHP namely to determine the relative weight and the rank or score. Two methods were utilized under FAHP to determine relative weight ; triangular and trapezoidal FAHP. Next type of FAHP was to determine the score of each alternative often carried out after triangular or trapezoidal FAHP. The second types of FAHP were Fuzzy TOPSIS, and VIKOR. These FAHPs were explained and steps to carry out were presented in this paper. In conclusion, all types of FAHP are compared in terms of computational time, number of steps and level of difficulty.